PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, VARIABILITAS PENDAPATAN, CORPORATE TAX RATE, DAN NON DEBT TAX SHIELD TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2015 - chairanisa natasha miraza; Said Muniruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The research examines the effect of institutional ownership, managerial ownership, income variability, corporate tax rate, and non debt tax shield. The sample of this research was taken from manufacture companies listed on Indonesia Stock Exchange at 2011-2015. The sample was taken using purposive sampling. The sample used was 22 companies. In order to test the hypothesis the statistical methods used was multiple linear regression analysis. Partially the result of this research shows that managerial ownership, income variability, corporate tax rate, and non debt tax shield have significant influence on capital structure, whereas institutional ownership has no significant effect on the dependent variable. Meanwhile in the simultaneous test, the five independent variables are seen to have significant influences to the capital structure.